Sítios cromossômicos instáveis e diversificação cariotípica em Loricariidae: análise citogenética e molecular - Glugoski, Larissa (2022)
Loricariidae includes species vulgarly known as armored catfishes. Cytogenetic data revealed wide chromosomal diversity in this family, resulted from both diploid number (2n) variation, because of centric fusion events, and structural chromosomal rearrangements, such as inversions, centromeric repositioning and translocations. The chromosomal rearrangements found in Loricariidae are associated with double strand DNA breaks at sites rich in repetitive sequences. The instability present in these regions is described as “evolutionary breakpoint regions” (EBRs), which are considered hotspots for chromosomal rearrangements, and would be involved with the 2n reduction in the group. However, there are still few studies that sought to characterize the unstable chromosomal sites that generate karyotypic evolution in Loricariidae. Previous studies with Rineloricaria showed that these sites were located in rDNAs clusters, or at adjacent areas. Thus, this work aimed to identify and characterize the DNA sequences present in sites prone to chromosomal breaks, aiming to understand the molecular mechanism of chromosomal rearrangements and karyotypic diversity present in Loricariidae specimens. In the present study, we analyzed 95 specimens belonging to two subfamilies: Hypostominae (Ancistrus aguaboensis 2n = 50; Ancistrus cf. multispinis 2n = 52) and Loricariinae (Rineloricaria latirostris 2n = 46 and 48; Rineloricaria pentamaculata 2n = 54, 55 and 56), collected in different hydrographic basins in the South, Southeast and Central west of Brazil. Classical and molecular cytogenetic techniques were used, such as comparative in situ hybridization of 5S and 18S ribosomal genes (rDNA), telomeric sequence (TTAGGG)n, single repeat sequences ((A)30, (CA)15, (GA)15, (CAT)10 and (CGG)10), in addition to the analysis of genomic data provided by Next-Generation Sequencing (NGS). The results obtained revealed that Ancistrus cf. multispinis (2n = 52 chromosomes) presents a karyotype considered basal for Ancistrini, while A. aguaboensis has 2n = 50 (first karyotypic description), resulting from Robertsonian fusion (Rb) events, triggered by double strand breaks and rearrangements at sites of rDNA 5S, corroborating previously data found in other species of the group. For R. latirostris, we obtained the repetitive fraction for the recognition of microsatellite sequences present in regions previously described as chromosomal fusion points. It was found that repetitive sequences such as rDNAs, hAT transposon, and microsatellite units are present in flanking regions of chromosome breakage sites in R. latirostris, and because they contain sites of paralogous sequences present in non-homologous chromosomes, these sequences may have acted as facilitators of Rb fusion events present in this group. Furthermore, the involvement of acrocentric chromosomes in Rb fusion events was discussed, with the participation of 5S rDNA and microsatellites, which culminated in the emergence of a numerical chromosomal polymorphism observed in specimens of R. pentamaculata from the Barra Grande River (2n = 54 to 56). The data presented for Rineloricaria corroborate studies that suggested that the 2n reduction is resulted from Rb fusion, with the decrease of subtelo/acrocentric chromosomes and the consequent formation of metacentric chromosomes, with or without ITS vestiges. In summary, it was demonstrated the accumulation of repetitive DNAs present in regions of chromosomal breaks and their potential involvement with the extensive chromosomes observed in Loricariidae, impacting the diversity and karyotypic evolution of the group.